The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.13001/1081-3810.2943
|View full text |Cite
|
Sign up to set email alerts
|

Open problems in the theory of completely positive and copositive matrices

Abstract: Abstract. We describe the main open problems which are currently of interest in the theory of copositive and completely positive matrices. We give motivation as to why these questions are relevant and provide a brief description of the state of the art in each open problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 63 publications
0
76
0
Order By: Relevance
“…for all j according to (7) and the sequence {x t } is bounded according to (i), we deduce further that {η tj } is bounded. By passing to a further subsequence if necessary, we may assume without loss of generality that η tj → η * for some η * .…”
Section: ⊓ ⊔mentioning
confidence: 61%
See 2 more Smart Citations
“…for all j according to (7) and the sequence {x t } is bounded according to (i), we deduce further that {η tj } is bounded. By passing to a further subsequence if necessary, we may assume without loss of generality that η tj → η * for some η * .…”
Section: ⊓ ⊔mentioning
confidence: 61%
“…where the last inequality follows from (7) with M = 0, (35), and the facts that x t − x * ≤ ǫ/2 and that F (x * ) < F (x t ) ≤ F (x N 1 ) < F (x * ) + ǫ (since t ≥ N 1 ). Dividing both sides of the above inequality by c 2 , taking square root, using the relation √ ab ≤ a+b 2 for any nonnegative numbers a and b and invoking the definition of C 1 , we obtain further that…”
Section: A Proof Of Theoremmentioning
confidence: 97%
See 1 more Smart Citation
“…, m) is impossible. Very recently, Zhang [29] showed that the CPP cone with dimension not less than 5 is not facially exposed, i.e., some of its faces are non-exposed (see also [6,13] for geometric properties of the CPP cone). Thus, our framework using COP(co(K ∩ J), Q 0 ) is more general than the work using (2) in [1,2,3,4,19].…”
Section: Relations To Existing Workmentioning
confidence: 99%
“…We use bold letters like v, w ∈ C n to denote vectors, non-bold uppercase letters like A, B ∈ M n (C) to denote matrices, and non-bold lowercase letters like c, d ∈ C to denote scalars. Subscripts on non-bold letters indicate particular entries of a vector or matrix (e.g., v 1 , v 2 , v 3 denote the first 3 coordinates of the vector v), while subscripts of bold letters denote particular vectors (e.g., v 1 , v 2 , v 3 are three vectors). Double subscripts are sometimes used to denote specific entries of vectors that are themselves denoted by subscripts (e.g., v 3,7 refers to the 7-th entry of the vector v 3 ).…”
Section: Mathematical Preliminariesmentioning
confidence: 99%